Selling translation rights in trade publishing : case studies of Dutch translations of Afrikaans fiction in the Netherlands and Belgium - Le Roux, Elizabeth Henriette (University of Pretoria, 2018)
Dissertation (MIT)--University of Pretoria, 2017.